Manajemen Kinerja dalam Prespektif SDM Modern di Badan Kepegawaian Daerah dan Pengembangan SDM Kabupaten Sikka - Maria Silvana Mariabel Carcia; Agnes Obeyane Longge; Yohanes Yuaniku; Carol Diego Fernandez (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Performance management plays a central role in improving the effectiveness and efficiency of organizations, both in the public and private sectors. In modern government, the increasing public demand for quality, transparent, and accountable public services has encouraged comprehensive bureaucratic reform. The State Civil Apparatus (ASN) is now positioned as an agent of development that must be adaptive, innovative, and results-oriented. Performance management is no longer just a compliance-based evaluation tool, but rather an integrated strategic approach to drive organizational success on an ongoing basis. In line with Armstrong's (2009) view, the focus of modern performance management lies on developing the capacity of individuals and teams to create optimal contributions to the achievement of organizational goals.